A Quantitative Analysis of the Balance of Payment Performance Using an Alternative Evaluation Approach: A Case of Zambia (1980 – 2020) - Mutambo, Benson; Musantu, John (American Journal of Economics, 2025)
Purpose: This paper seeks to evaluate Zambia's balance of payment performance from 1980 to 2020 and thus provide a nuanced and in-depth assessment that offers a comprehensive understanding of its balance of payment dynamics beyond traditional methods. Materials and Methods: The study employed the Vector Error Correction (VEC) model to integrate monetarist, elasticity, and Keynesian theories. Thus examine the short-run and long-run impact of Exchange Rate, Inflation Rate, Interest Rate, External Credit, Gross Domestic Product, and Foreign Direct Investment on Balance of Payment. Findings: The empirical analysis reveals that exchange rate fluctuations, foreign direct investment (FDI), and external credit exert modest short-run effects on the BOP. However, in the long run, these factors demonstrate statistically significant impacts, highlighting their critical role in shaping Zambia’s external account dynamics. The findings indicate that exchange rate depreciation enhances export competitiveness by making exports cheaper while increasing the cost of imports. FDI inflows contribute positively to the capital account, supporting the balance of payment. Conversely, higher reliance on external credit is associated with elevated debt servicing costs, adversely affecting the BOP. Furthermore, domestic inflation influences trade dynamics by making local goods relatively expensive, thereby reducing imports, while GDP growth spurs higher import demand due to increased domestic consumption. Higher interest rates, on the other hand, may suppress borrowing, thus reducing liquidity in the economy. Implications to Theory, Practice and Policy: These results underscore the need for Zambia to adopt balanced macroeconomic policies that address structural vulnerabilities in the BOP. Key policy recommendations include inflation targeting to maintain price stability, exchange rate stabilization to foster trade competitiveness, diversification of FDI inflows to reduce dependency on a single sector, sustainable external credit management to mitigate debt burdens, and an export-oriented growth strategy to enhance foreign exchange earnings. By pursuing these measures, Zambia can strengthen its economic stability, sustain long-term growth, and reduce susceptibility to external shocks.